Follow‐up of isolated neutron star candidates from the eROSITA survey. Issue 2 (8th March 2017) - Pires, A. M.; Schwope, A. D.; Motch, C.
Abstract : Peculiar groups of X‐ray emitting isolated neutron stars, which include magnetars, the "magnificent seven", and central compact objects in supernova remnants, escape detection in standard pulsar surveys. Yet, they constitute a key element in understanding the neutron star evolution and phenomenology. Their use in population studies in the galactic scale has been hindered by the rarity of their detection. The all‐sky survey of the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on‐board the forthcoming Spectrum‐Roentgen‐Gamma (SRG) mission has the unique potential to unveil the X‐ray faint part of the population and constrain evolutionary models. To create a forecast for the 4‐year all‐sky survey, we perform Monte Carlo simulations of a population synthesis model, where we follow the evolutionary tracks of thermally emitting neutron stars in the Milky Way and test their detectability. In this paper, we discuss strategies for pinpointing the most promising candidates for follow‐up observing campaigns using current and future facilities.